Corynebacterium silvaticum sp. nov., a unique group of NTTB corynebacteria in wild boar and roe deer. Issue 6 (5th June 2020) - Dangel, Alexandra; Berger, Anja; Rau, Jörg; Eisenberg, Tobias; Kämpfer, Peter; Margos, Gabriele; Contzen, Matthias; Busse, Hans-Jürgen; Konrad, Regina; Peters, Martin; Sting, Reinhard; Sing, Andreas
Abstract : A total of 34 Corynebacterium sp. strains were isolated from caseous lymph node abscesses of wild boar and roe deer in different regions of Germany. They showed slow growth on Columbia sheep blood agar and sparse growth on Hoyle's tellurite agar. Cellular fatty acid analysis allocated them in the C. diphtheriae group of genus Corynebacterium . MALDI-TOF MS using specific database extensions and rpoB sequencing resulted in classification as C. ulcerans . Their quinone system is similar to C. ulcerans, with major menaquinone MK-8(H2). Their complex polar lipid profile includes major lipids phosphatidylinositol, phosphatidylinositol-mannoside, diphosphatidylglycerol, but also unidentified glycolipids, distinguishing them clearly from C. ulcerans . They ferment glucose, ribose and maltose (like C. ulcerans ), but do not utilise d -xylose, mannitol, lactose, sucrose and glycogen (like C. pseudotuberculosis ). They showed activity of catalase, urease and phospholipase D, but variable results for alkaline phosphatase and alpha-glucosidase. All were non-toxigenic, tox gene bearing and susceptible to clindamycin, penicillin and erythromycin. In 16SrRNA gene and RpoB protein phylogenies the strains formed distinct brancheswith C. ulcerans as nearest relative.Whole genome sequencing revealed the unique sequence type 578, a distinctbranch in pangenomic core genome MLST, average nucleotide identities <91%, enhancedgenome sizes (2.55 Mbp) and G/C content (54.4 mol%) compared to related species.These results suggest that the strains represent a novel species, for which wepropose the name Corynebactriumsilvaticum sp. nov., based on their first isolation from forest-dwellinggame animals. The type strain isKL0182 T (= CVUAS 4292 T = DSM 109166 T = LMG 31313 T = CIP 111 672 T ).